OPPORTUNITIES FOR ENHANCING POPULATION FINANCIAL LITERACY THROUGH DIGITAL TECHNOLOGIES - Azlarova Mushtariybegim Abror qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The rapid proliferation of digital technologies — including mobile applications, artificial intelligence, gamification platforms, and open online courses — has created unprecedented opportunities to scale financial literacy education across previously unreachable populations. This paper systematically reviews 163 empirical studies and 29 national digital financial literacy programs published between 2015 and 2024 across 57 countries, supplemented by original survey data from 4,800 respondents across five income groups. We find that digital delivery modalities outperform traditional classroom instruction by an average effect size of Hedges’ g = 0.52 on financial knowledge outcomes, with AI-personalized learning platforms demonstrating the strongest effects (g = 0.74). The global EdFinTech market has grown from USD 1.2 billion in 2018 to an estimated USD 19.8 billion in 2024, serving over 920 million users. Mobile-first programs show particular efficacy in low- and middle-income country (LMIC) contexts, where smartphone penetration has surpassed 60% even in rural areas. We identify five enabling conditions for effective digital financial literacy programs: digital access equity, culturally adaptive content, behavioral design integration, institutional trust-building, and evidence-based iteration. Our analysis reveals that a 10-percentage-point increase in digital financial literacy adoption at the national level is associated with a 4.7-point increase in formal financial account ownership and a 3.2-point decline in reliance on informal financial services. These findings have significant implications for policymakers, edtech developers, financial regulators, and development finance institutions committed to achieving universal financial inclusion.